Factors Influencing Hospital Information System User Acceptance Based on UTAUT (Unified Theory of Acceptance and Use of Technology) Model - Lidhah Sutramanden Astriaka; Firman Pribadi; Winny Setyonugroho (Jurnal Admmirasi, 2022)
Background: The success of implementing a hospital information system depends on its users’ acceptance. The UTAUT model can help identify the factors that determine the intentions and attitudes of information system users. Objective: To identify and analyze the factors influencing the acceptance of hospital information system users based on the UTAUT model. Methods: This study is a literature review by searching through the Pubmed and Sciencedirect electronic databases using a combination of keywords in articles published in 2013-2022, analyzing the acceptance factors of the hospital information system with the UTAUT model, speaking English and meeting the inclusion criteria. The review process is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Results: Ten articles showed mixed findings. The influence of the four critical constructs of performance expectancy, effort expectancy, social influence, and facilitating conditions on behavioral intention and use behavior/actual use can be different because it is determined by the research location, respondent demographics, and the way the UTAUT model is applied. Conclusion: The UTAUT model can explain the factors that affect the acceptance of hospital information system users.